Digital-twin enabled evacuation to improve individual and community resilience of building occupants against indoor Fires: Framework and route-finding algorithm - Jonathan Koon Ngee Tan; Shuai Zhang; Adrian Wing-Keung Law; Sai Hung Cheung (Developments in the Built Environment)
During indoor fires, building occupants are typically not guided with the optimal evacuation routes according to the up-to-date situation and suffer more health damage consequently. In this study, we propose a framework for the Fire Resilience Digital Twin (FRDT), a digital-twin enabled evacuation guidance system which improves the fire resilience of occupants by providing them with optimal evacuation routes in real time. The quantification metrics for real-time fire resilience of occupants were first established. Subsequently, a route-finding algorithm based on the established metrics was proposed to enable the FRDT to generate personalized evacuation routes optimized for both individual and community fire resilience, defined in terms of health damage and total evacuation time, respectively. Simulations of 500 occupants evacuating from a fire in an underground mall with and without guidance from a FRDT prototype showed that the prototype improved individual and community fire resilience by 6 %–64 % and 14 %, respectively.